2021
DOI: 10.1016/j.bpj.2021.06.042
|View full text |Cite|
|
Sign up to set email alerts
|

Reaction intermediate rotation during the decarboxylation of coproheme to heme b in C. diphtheriae

Abstract: Monoderm bacteria utilize coproheme decarboxylases (ChdCs) to generate heme b by a stepwise decarboxylation of two propionate groups of iron coproporphyrin III (coproheme), forming two vinyl groups. This work focuses on actinobacterial ChdC from Corynebacterium diphtheriae (CdChdC) to elucidate the hydrogen peroxide-mediated decarboxylation of coproheme via monovinyl monopropionyl deuteroheme (MMD) to heme b, with the principal aim being to understand the reorientation mechanism of MMD during turnover. Wild-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(39 citation statements)
references
References 36 publications
1
38
0
Order By: Relevance
“…Since the experiment results indicated that Tyr145 also engages in p4 decarboxylation, it is rational to speculate that, after the decarboxylation of p2, harderoheme experiences reorientation to place p4 toward Tyr145. Such a process could be accomplished either through the intermediate harderoheme rotation along the Fe–N ε(His171) axis or through a harderoheme release–rebinding mechanism [ 23 , 24 , 25 ]. In a recent study, by mutating His118, which is located between the p6 and p7 side chains, to a bulkier phenylalanine, Hofbauer found that the His118Phe mutant of CdChdC was unable to perform the second decarboxylation reaction of p4 [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Since the experiment results indicated that Tyr145 also engages in p4 decarboxylation, it is rational to speculate that, after the decarboxylation of p2, harderoheme experiences reorientation to place p4 toward Tyr145. Such a process could be accomplished either through the intermediate harderoheme rotation along the Fe–N ε(His171) axis or through a harderoheme release–rebinding mechanism [ 23 , 24 , 25 ]. In a recent study, by mutating His118, which is located between the p6 and p7 side chains, to a bulkier phenylalanine, Hofbauer found that the His118Phe mutant of CdChdC was unable to perform the second decarboxylation reaction of p4 [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Such a process could be accomplished either through the intermediate harderoheme rotation along the Fe–N ε(His171) axis or through a harderoheme release–rebinding mechanism [ 23 , 24 , 25 ]. In a recent study, by mutating His118, which is located between the p6 and p7 side chains, to a bulkier phenylalanine, Hofbauer found that the His118Phe mutant of CdChdC was unable to perform the second decarboxylation reaction of p4 [ 25 ]. However, the His118Ala mutation did not interrupt the production of heme b [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…H118, unique in actinobacterial ChdCds, is part of a flexible loop, linking the N- and the C-terminal domain of one subunit in ChdCs ( Hofbauer et al, 2021 ). In this variant, the catalytic tyrosine (Y135) of Cd ChdC is positioned correctly to facilitate decarboxylation of p2 but due to steric hindrance, the reorientation of the three-propionate intermediate is prohibited and therefore no decarboxylation of p4 occurs ( Sebastiani et al, 2021 ). In this study, we designed variants where another tyrosine is introduced at the site of p4 (W183Y).…”
Section: Introductionmentioning
confidence: 99%